{ x ˙ 1 = 3 x 1 − x 2 + u x ˙ 2 = 5 x 1 − x 2
Let x 1 , x 2 and u be functions of time t satisfying the system of equations above which governs the behaviour of an arbitrary physical system. The energy of this physical system is:
E = 2 x 1 2 + x 2 2
The goal of this question is to choose u which is dependent on the variables x 1 and x 2 such that the energy of the system always decreases (for any non-zero initial conditions) with time. Make the appropriate choice for u among the given options.
Bonus: What happens to the energy when u = 0 ? What is the significant observation one can make through this problem?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Thanks for the solution. Your explanation of the significance of this problem really sums up why I enjoy control theory. The idea of 'making nature dance to our tunes' using mathematics is one I find really cool. There will be more variants coming up.
Given that E = 2 x 1 2 + x 2 2 , ⟹ E ˙ = x 1 x ˙ 1 + x 2 x ˙ 2 . For the energy of the system to be always decreasing then E ˙ < 0 . That is:
x 1 x ˙ 1 + x 2 x ˙ 2 ⟹ x 1 ( 3 x 1 − x 2 + u ) + x 2 ( 5 x 1 − x 2 ) 3 x 1 2 + 4 x 1 x 2 + a x 1 2 + b x 1 x 2 − x 2 2 − x 1 2 − x 2 2 < 0 < 0 < 0 < 0 Let u = a x 1 + b x 2 Note that LHS = − x 2 2 , when a = − 3 , b = − 4 when u = − 4 x 1 − 4 x 2
Problem Loading...
Note Loading...
Set Loading...
Time-differentiating the energy and substituting in the differential equations, we get the following requirement:
3 x 1 2 + 4 x 1 x 2 + u x 1 − x 2 2 < 0
What remains is to plug in the candidate u expressions and see whether the results satisfy the condition. What we want is for the resulting expression to consist purely of − x 1 2 and − x 2 2 terms.
For example, u = − 4 x 1 − 4 x 2 yields:
3 x 1 2 + 4 x 1 x 2 + ( − 4 x 1 − 4 x 2 ) x 1 − x 2 2 = 3 x 1 2 + 4 x 1 x 2 + − 4 x 1 2 − 4 x 1 x 2 − x 2 2 = 3 x 1 2 − 4 x 1 2 − x 2 2 = − x 1 2 − x 2 2
So this works. Recall that this system is inherently unstable due to its eigenvalues having positive real parts. For u = 0 , the system diverges. The lesson is that we can stabilize an inherently unstable system by applying a properly-chosen forcing function.